PEMBUATAN KONTEN INSTAGRAM OSIS SMK WALISONGO SEMARANG BERBANTUAN CAPCUT - Laksono, Agus Edy; Watie, Errika Dwi Setya; Fanani, Fajriannoor; Rahmah, Hilda (Jurnal Abdikaryasakti, 2025)
Instagram utilization is able to meet followers’ information needs, provide both social and commercial benefits for users, and serve as a medium to attract public interest in better understanding the user or content provider. In the field of education, Instagram can also be used for various purposes such as learning media and promotional tools. SMK Walisongo Semarang, the partner in this community service program, already manages two Instagram accounts: @smkwalisongoofficial and @osis_skawas. The @smkwalisongoofficial account is managed by teachers and staff, while @osis_skawas is managed by student council (OSIS) members. The focus of this program is the @osis_skawas account, which was created in 2023 and currently has 93 posts and 170 followers. Unfortunately, within approximately two years, the account has only published that number of posts, consisting of 81 photos with captions and 12 reels. According to one of the community service team members, the account’s content has remained limited and monotonous since last year, indicating low activity and lack of development from the administrators. Based on interviews with the Vice Principal of Student Affairs, the administrators faced challenges in content creation, both technically and in terms of ideas. Through lecture, discussion, and hands-on practice methods, this training had a positive impact on the students of SMK Walisongo Semarang. Knowledge and skills related to the types of content, ways to create and edit, motivation enhancement, and effective content creation strategies were provided to the target audience, enabling them to understand how to increase engagement in each post. In addition, the use of CapCut in video production was also discussed, equipping them with sufficient skills to edit videos and develop the @osis_skawas account.